RANCANG BANGUN ALAT PENGUKUR KADAR ALKOHOL DAN SUHU OTOMATIS BERBASIS INTERNET OF THINGS - Afiat, Dimas Fajar (Teknik Elektro Politeknik Negeri Balikapapan, 2025)
Alcohol abuse has become a problem in Indonesia. There are many crimes such as murder, adultery, and even vehicle accidents on the highway caused by drivers consuming alcoholic beverages in excess. In this decade, research has been conducted on the detection of alcohol levels in a person. The research was conducted using the MQ-3 sensor. And during this pandemic, body temperature is a reference for people to measure whether the person is indicated by the corona virus or not. Non-contact body temperature sensors are very important for humans to measure body temperature quickly and practically. One of the sensors that can be used to measure non-contact body temperature sensors is the MLX90614. The MLX90614 sensor has two outputs, namely room temperature and object temperature.